Analisis Pengaruh Batu Kapur Puger, Jember sebagai Substitusi Agregat Kelas B Berdasarkan Uji CBR - Septiana Dwi Wahyuni; Ilanka Cahya Dewi; Arief Alihudien (Jurnal Rekayasa Infrastruktur HEXAGON, 2026)
The use of local materials as an alternative to road pavement aggregates can be a solution for improving resource efficiency. Limestone, which is abundantly available in Puger Subdistrict, Jember Regency, has the potential to be used as a substitute for Class B aggregate. This study aims to analyze the effect of limestone substitution on the compaction characteristics and California Bearing Ratio (CBR) values of Class B aggregate. The substitution rates used were 0%, 5%, 10%, and 20%. The tests included sieve analysis, the Modified Proctor test, and the soaked California Bearing Ratio (CBR) test. The results showed that all mixture variations still met the gradation specifications for Class B aggregate. However, an increase in the limestone content caused the maximum dry unit weight to decrease from 2.01 g/cm³ to 1.88 g/cm³, while the optimum moisture content increased from 7.27% to 7.57%. The CBR value also decreased from 63.90% in the mixture without substitution to 55.90% at a 20% substitution rate. Regression analysis revealed a strong relationship between the limestone content and the CBR value, with a coefficient of determination (R²) of 0.929. Based on the research results, the use of limestone as a substitute for Class B aggregate is still recommended up to a 10% substitution rate, as it continues to meet the minimum CBR requirements according to the 2025 General Specifications for Road Construction